Multiple lesions of gastrointestinal tract invasion by monomorphic epitheliotropic intestinal T-cell lymphoma, accompanied by duodenal and intestinal enteropathy-like lesions and microscopic lymphocytic proctocolitis: a case series. Issue 1 (December 2016) - Ishibashi, Hideki; Nimura, Satoshi; Kayashima, Yoshiyuki; Takamatsu, Yasushi; Aoyagi, Kunihiko; Harada, Naohiko; Kadowaki, Masanori; Kamio, Takihiko; Sakisaka, Shotaro; Takeshita, Morishige
Abstract Background In East Asia, monomorphic epitheliotropic intestinal T-cell lymphoma (MEITL), previously known as type II enteropathy-associated T-cell lymphoma (EATL), occurs more frequently than type I EATL, and coeliac disease is rare. Case presentation Here we present four cases of MEITL in Japanese patients, including the endoscopic and pathological findings of their duodenal and colorectal lesions. Tumor specimens obtained from duodenal, intestinal, and colorectal biopsies in all four patients showed a diffuse intramucosal infiltration of small to/or medium-sized lymphoma cells and numerous atypical intraepithelial lymphocytes (IELs). These cells were immunohistologically positive for CD103, CD3, CD7, CD8, CD56, and T-cell intracellular antigen-1. Upper and lower gastrointestinal and antegrade double-balloon endoscopy revealed foci of edematous mucosa, with or without villous atrophy, in the non-neoplastic mucosa. Histological studies demonstrated duodenal and intestinal enteropathy-like lesions as well as microscopic (lymphocytic) proctocolitis with increased CD3- and CD8-positive and CD56-negative T-IELs in all four patients. The clinicopathological findings of the non-neoplastic lesions were similar to those characteristic of coeliac disease, suggesting that variants of coeliac disease may be present in the prodromal lesions of MEITL. Conclusions Our study supports the need for random gastrointestinal biopsies to determine tumor spread, the features of MEITL in the particular patients, and the presence of prodromal non-neoplastic lesions.